Indexing policy of journals on Information Science: a study of the guidelines for assignment of keywords to articles - Oliveira, Lais Pereira de [UNESP] (2020)
This paper analyzes the indexing policies of Brazilian journals on Information Science. It considers the scarce approach to the subject in the context of scientific communication, as well as the pragmatic need to systematize the action of assigning keywords by the author of the publication. It aims to analyze the online guidelines for assignment of keywords to articles during the submission process. It is a descriptive research that follows a qualitative and quantitative methodology. It can be characterized as a documentary research as the data was collected from the publication policies and guidelines for authors that are made available by the journals. We also conducted a content analysis to systematize the collected data. The results reveal the existence of guidelines related to the number of terms, mostly connected to selection in indexing. This was not the case for the specifications of the depth of terms and the indexing language, despite the referral to the latter in a total of five journals that use a controlled language. We conclude that Brazilian journals of Information Science need to pay a greater attention to the implementation of indexing policies in order to provide a greater assertiveness to the authors, especially during the attribution of keywords.